Implementation of Islamic corporate governance and competitive advantage in SMEs: A systematic literature review approach - Pahlevi, Reza Widhar (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2022)
In the case of Indonesia, research related to good governance in SMEs is categorized as relatively new and has received little attention. Attention to SMEs is deemed inadequate, while the development of Sharia-based SMEs. The development of Sharia-based SMEs should be the basis for building a solid halal industry construction. SMEs must be developed in order to create a prosperous society. However, whether the method and type of business taken in fulfilling the needs of life are in accordance with Islamic rules, that is the problem and must be a concern for business actors. In running an SMEs business, of course there are limitations in selecting and sorting the products that will be produced by business actors. This study comprehensively examines the topic of governance from an Islamic perspective through analysis of corporate models and conceptual empirical research. The next stage of this research is to review previous research that became a reference and show the things that happened in the literature both theoretically and empirically. Literature study, this research shows the main findings, namely the emergence of uncertainty in the results of the application of governance from an Islamic perspective and competitive advantage in SMEs. Previous researchers conducted related research showing different research results so that further research will be carried out for previous researchers by integrating the comparison pattern between the competitive advantages of conventional SMEs with sharia and the application of corporate governance in SMEs.